2022
DOI: 10.1039/d1ra08249c
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion behavior and mechanism of X80 steel in silty soil under the combined effect of salt and temperature

Abstract: The combined effect of salt and temperature on the corrosion behavior of X80 steel in silty soil was studied by microscopic and spectroscopic characterization techniques and electrochemical measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Thus, the moisture and ions in the soil were more easily adsorbed by the droplets on the surface of the X70 steel specimens, which facilitated the corrosion reaction. The deposition of corrosion products formed at different times during the corrosion process resulted in the significant delamination of some corrosion product aggregates [ 64 ]. As shown by the macroscopic image in Figure 17 , the loose corrosion products on the surface of the X70 steel specimen combined with the fine sticky particles in the soil.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the moisture and ions in the soil were more easily adsorbed by the droplets on the surface of the X70 steel specimens, which facilitated the corrosion reaction. The deposition of corrosion products formed at different times during the corrosion process resulted in the significant delamination of some corrosion product aggregates [ 64 ]. As shown by the macroscopic image in Figure 17 , the loose corrosion products on the surface of the X70 steel specimen combined with the fine sticky particles in the soil.…”
Section: Resultsmentioning
confidence: 99%
“…The open circuit potential in this test can reect the thermodynamic 4) indicate that the corrosion systems were in aerobic state. 21 The OCP values tended to be stable with time. OCP values gradually increased with the decrease of temperature, and the change range of OCP at 0 C and −5 C was larger.…”
Section: Open Circuit Potential Curvesmentioning
confidence: 99%
“…44 The corrosion behaviour of steel in the soil below the freezing point was related to its surface unfrozen liquid layer. 21 The appearance of this liquid layer was due to the premelting phenomenon on the surface of the solid and ice layer, which usually occurs at the interface between the electrode and the ice. 45,46 Water molecules and ions were able to ow freely in this layer.…”
Section: Changes In Soil Thermodynamics During Coolingmentioning
confidence: 99%
“…They found that 10% moisture content enabled the X60 steel to reach a critical corrosion rate, and the corrosion caused by the soil in these three cities was evaluated under the condition of critical moisture content. X. Bai et al 15 studied the corrosion behaviour of X80 pipeline steel in silty saline soil containing chloride ions at different temperatures. They found that the corrosion kinetics of the steel at negative temperatures decreased with decreasing unfrozen moisture content in the soil, and the corrosion products were mainly iron oxide.…”
Section: Introductionmentioning
confidence: 99%